Traditional food consumption pattern and nutritional status of Oraons: An Asian Indian indigenous community - Bisai, Samiran; Dutta, Sarnali; Das Mohapatra, Pradeep K. (Frontiers in Sustainable Food Systems, 2023)
Introduction: Eating is an intensely social activity and the most perfect cultural artifact, the outcome of a detailed process of differentiation. Food has a positive effect on a person’s health, physical performance, or state of mind. The nutritional characteristics of the diet have an enormous influence on the development and health of individuals. Methods: This explanatory cross-sectional study was conducted during January – July, 2018 on traditional food practices of Oraon following one-to-one interview, focus group discussions and anthropometric measurements. Individual food recipe and their documentation, from collection to preparation has been undertaken. To assessed nutrient intake, 24-hour dietary recall method has been used and information has been collected from 200 Oraon families. A total of 466 adults’ males and females were measured for nutritional assessment. All anthropometric measurements were made and recorded by standard method. Adult nutritional status was assessed by body mass index (BMI). Nutrient content of handia is also investigated. Results: Mean (SD) height, weight and MUAC and BMI of Oraons peoples were amylase. Sex combined, overall prevalence of chronic energy deficiency (CED; BMI<18.5kg/m2) was 39% (male=37%, female=40.3%). The prevalence of overweight and obese (BMI≥25.0kg/m2) was 7.1% found among female only. Average energy intake was 2290 kcal/cu/d. It is noteworthy to mention here to a large extent food and nutrient consumption among Oraon tribe was comparatively better than the PVTGs of West Bengal and almost similar RDA/RDI as reflect by their nutritional status. Root and tubers consumption is very high. Animal protein intake in terms of Periwinkles is common among Oraons. Nutrient rich fermented rice beer consumption is found to be remarkable. Conclusion: Present study also indicates that due admixing of other communities there has been a huge transition in their indigenous pattern of food consumption. Regional need-based planning with proper effective intervention programs should be implemented. Proper maintenance of kitchen gardens with domestication of wild consumable collectables seeds, tubers etc. may prove to be helpful. Moreover, promotion of macronutrient fortified handia/rice bear may be beneficial to fight hidden hunger among adults as handia is their cultural drinks having medicinal effects.